Respuesta :
Answer:
y= -1
Step-by-step Explanation:
3(5y +2)-y=2(y-3)
Distribute- 15y +6-y=2y -6
Combine variables- 15y-2y-y=-6-6
Add everything together- 12y= -12
Divide- y= -1
Answer:
y = -1
Step-by-step explanation:
Step 1. Expand the brackets.
3(5y + 2) - y = 2(y - 3)
(3 x 5y) + (3 x 2) - y = (2 x y) - (2 x 3)
15y + 6 - y = 2y - 6
Step 2. Simplify the expanded brackets (not always necessary but is in this case).
15y + 6 - y = 15y - y + 6 = 14y + 6
So
14y + 6 = 2y - 6
Step 3. Solve the equation.
14y + 6 = 2y - 6
+ 6 to both sides
14y + 12 = 2y
- 14y from both sides
12 = -12y
÷ 12 on both sides
1 = -y
flip the negative
-1 = y
Step 3. Write your answer.
y = -1